Nanofiltration Membranes: Recent Advances and Environmental Applications - Peydayesh, Mohammad (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book, titled "Nanofiltration Membranes: Recent Advances and Environmental Applications", aims to assess the recent developments and advances in all the aspects related to nanofiltration (NF) technology and its environmental applications. This book has ten articles, including eight research articles and two reviews. Various topics are discussed, including fabrication of organic and inorganic NF membranes, tailoring NF membranes' surface properties, the application of NF in side-stream valorization, using NF technology in combination with other membrane technologies such as ultrafiltration (UF) and reverse osmosis (RO), wide-range applications of NF for removing organic and inorganic pollutants and viruses, and a detailed sustainability assessment of the use of NF technology via life cycle assessment (LCA).